Effectiveness of a sealscarer in deterring harbour porpoises (Phocoena phocoena) and its application as a mitigation measure during offshore pile driving : final report ... - BioConsult SH GmbH (Technische Informationsbibliothek u. Universitätsbibliothek, 2012)
Ill., graph. Darst., Kt. ...